Systematic Literature Review on the Politics of Educational Dualism and its Implications for Budget and Well-Being Policies - Achmad Maulidi; Nur Afifah Khurin Maknin; Muliatul Maghfiroh; Pudyas Tataquna Raniya; Masdar Hilmy; Iksan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Education dualism cannot be separated from the historical aspects of the colonial era. This policy continues to be debated among academics, particularly with regard to budget policies and the quality of education. This study aims to describe the political implications of education dualism on budget and welfare policies. This research uses a systematic literature review approach comprising four stages: identification, screening, eligibility and conclusions. A total of 626 data items were collected, with 226 items collected from the Scopus database and 226 items from the Google Scholar database. All stages of data collection, screening and reporting were guided by PRISMA. The results showed that the political implications of dualism triggered inequality in the budget and welfare: the budget allocation for religious education was smaller than for general education, which also affected the welfare of educators. Although the government made efforts to equalise, policies between ministries often did not support each other. This research contributes by providing a concrete overview of how the political implications of dualism affect education budget policies and educators' well-being, encouraging the government and stakeholders to implement education system reforms that are more harmonious, efficient and socially just.